PERBEDAAN TAKTIK STRATEGI MENYERANG DENGAN SPIKE ELIT ATLET BOLAVOLI PELAJAR INDONESIA DAN MALAYSIA PADA PERTANDINGAN ASEAN SCHOOL GAMES KE-11 TAHUN 2019 (Indonesian Journal for Physical Education and Sport, 2020)
The purpose of this study was to determine the differences in attack strategy tactics with Indonesian and Malaysian student volleyball athletes in the 11th Asean School Games in 2019. The method used in this study was descriptive quantitative with structured observation techniques. The population of this research is the Indonesian team and the Malaysian team in the 2019 ASEAN School Games competition. The sample in this study was the Indonesian men's and women's volleyball athlete team and the 48 Malaysian male and female team of athletes. Research results covering the most attacking aspect aspects used by Indonesian men's teams are front spikes (144) Indonesian women's teams front spikes (144), Malaysian men's teams are front spikes (146) and Malaysian women's teams front spikes (138). Regional aspects were most attacked by the Indonesian men's team to position 1 (80) Indonesian women's team to position 6 (105), Malaysian men's team to position 5 (91) and Malaysian women's team to position 6 (100). The most effective aspects of the position of the spike used by the Indonesian men's team are the middle spike (67.31%) Indonesian women's team the middle spike (67.31%), the Malaysian spike men's team (65.85%) and the rear Malaysia spike women's team (60.53%). The conclusion from the results of this study is that there are differences in strategy tactics carried out by the two countries, and the Indonesian team has a better percentage level compared to the Malaysian team.